Implantation Window and Angiogenesis. Issue 12 (31st May 2017) - Karizbodagh, Mostafa Peyvandi; Rashidi, Bahman; Sahebkar, Amirhossein; Masoudifar, Aria; Mirzaei, Hamed
ABSTRACT: In recent decades, infertility is one of the health problems worldwide. One of the most crucial events in reproductive period is implantation window (IW). In the time after IW period, the embryo cannot connect to the endometrium; therefore the most critical issue for successful implantation is timely entrance of embryo to the uterine cavity during the IW. Implantation failure is responsible for many cases of infertility and is the most important limiting factor for achieving a successful outcome using the assisted reproductive techniques (ART). The aim of this study was to investigate the receptivity of the endometrium and factors affecting it with emphasizing on the role of angiogenesis. Interaction between the embryo and the endometrium is affected by molecular interactions among cytokines, growth factors, hormones, and cell adhesion molecules, causing endometrial receptivity. Also, angiogenesis is a process that has an important role in human implantation. Estrogen and progesterone hormones are two important regulation keys in angiogenesis and implantation process. It is expected that effective and stimulating drugs of angiogenesis can improve the characteristics of endometrial receptivity and prevent implantation failure in ART. It is hoped that with recent advances in the field of molecular medicine, improvement of angiogenesis in human endometrium and prevention of the implantation failure be achieved. Here, we summarized various factors could affect on endometrial receptivity and the role of them on angiogenesis. J. Cell. Biochem. 118: 4141–4151, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Implantation failure is responsible for many cases of infertility and is the most important limiting factor against achieving successful outcomes in using the ART. The implantation process requires bilateral cooperation of the embryo and endometrium.